Perubahan Sosial Dalam Upacara Adat Kematian Pada Etnis Batak Toba di Tapanuli Utara - Harisan Boni Firmando (Sosial Budaya, 2020)
The traditional ceremony for the death of the ethnic Toba Batak is a sacred activity and is a hereditary heritage carried out to date. Death ceremonies vary according to the situation and place of the deceased. At present there are some changes in the implementation of the ceremonies of death after the Batak people in their hometown interact with people from other regions. The informants in this study are traditional leaders, religious leaders, people who have performed traditional death ceremonies in their hometown, namely North Tapanuli. This study found that the implementation of the stages of the event at the traditional ceremonies of death that occurred at this time experienced a development where the existing customs became more diverse. Existing traditional rites have begun to change, this change gave birth to a new habit. The occurrence of these new habits is caused by a variety of things, namely the influence of the majority of teachings adopted by the Toba Batak community, space and time that has changed, and the actualization of status and power to achieve life goals. Various strategies carried out by agents to achieve life goals by changing existing structures. Changes in the structure can be seen in changes in the implementation of ritual ceremonies which are organized repeatedly, where various practices of traditional ceremonies of death are always produced and reproduced, so they will still exist. Along with various developments, in the future the implementation of the traditional ceremony of death will experience challenges, namely consumerism, materialism and decreased solidarity. However, the challenge is not a barrier to continue carrying out traditional ceremonies.